Metode Group Investigation (Konsep dan Aplikasinya dalam Pembelajaran) - Imam Nur Hakim (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2013)
Abstract: Group Investigation is part of the cooperative learning method. Group investigation as a method has its own theory based on the ideas of Piaget, Brunner and Papert in which they stressedthe importance of active participation in the construction and exploration of knowledge and understanding. This paper will examine the meaning of the group investigation methods, the implementation method of group investigation, and the advantages and disadvantages of group investigation method. Keywords : methods, group investigation, cooperative learning.